Transcriptional analysis in bacteriophage Fc02 of Pseudomonas aeruginosa revealed two overlapping genes with exclusion activity - Ramírez-Sánchez, Irais; Magos-Castro, Marco; Guarneros, Gabriel (Frontiers in Microbiology, 2023)
Little is known about the gene expression program during the lysogenic and lytic cycles of temperate bacteriophages in Pseudomonas aeruginosa. To investigate this issue, we developed a thermo-sensitive repressor mutant in a lysogen and analyzed the phage transcriptional program by strand specific RNAseq before and after thermo-induction. As expected, the repressor gene located on the phage DNA forward strand, is transcribed in the lysogen at the permissive temperature of 30ºC. Upstream the promoter gene, we noticed the presence of two overlapped ORFs apparently in the same transcript, one ORF is a gene that encodes a protein of 7.9 kDa mediating exclusion of various super-infecting phages. The other ORF, placed in an alternate reading frame, with a possible AUG initiation codon at 25 n downstream the AUG of the first gene, is expected to encode a 20.7 kDa polypeptide of yet unknown function. Upon lifting repression at 40ºC, starts transcription of a lysis operon from a promoter on the reverse phage DNA strand. The first gene in the operon is a homolog of the antirepresor ner, a common gene in the lysis-lysogeny regulation region of other phages. Interestingly, the next gene after ner is gene 10, that on the reverse strand, overlaps the overlapped genes on the forward strand. Curiously gene 10 has also been proposed as a superinfection exclusion gene. Strand specific RNAseq also has uncover the transcription succession of gene modules expressed during the phage lytic stage.